Dissimilar forests along the Rio Doce watershed call for multiple restoration references to avoid biotic homogenization - Ramos, Letícia; Negreiros, Daniel; Goulart, Fernando Figueiredo; Figueiredo, João Carlos Gomes; Kenedy-Siqueira, Walisson; Toma, Tiago Shizen Pacheco; Justino, Wénita de Souza; Maia, Renata A.; de Oliveira, Jéssica Tetzner; Oki, Yumi; Barbosa, Milton; Aguilar, Ramiro; et al. (The Science of the total environment, 2024)
An environmental disaster caused by the rupture of a mining tailings dam has impacted a large area of the Rio Doce watershed in the Brazilian Atlantic Forest, resulting in unprecedented damage at spatial and temporal scales. The Atlantic Forest is one of the world's most important biodiversity hotspots. A long history of land use conversion has resulted in a highly fragmented landscape. Despite numerous restoration initiatives, these efforts have often biased criteria and use limited species assemblages. We conducted a comprehensive synthesis of the plant community in riparian forests along the Rio Doce watershed. Our work detailed vegetation composition (tree and sapling strata) and examined its relationship with edaphic and landscape factors, aiming to inform restoration projects with scientifically robust knowledge. A total of 4906 individuals from the tree strata and 4565 individuals from the sapling strata were recorded, representing a total of 1192 species from 75 families. Only 0.8% of the tree species and 0.5% of the sapling species occurred in all sampled sectors, with over 84% of the species occurring in a single watershed sector for both strata. We observed a high species heterogeneity modulated by turnover (92.3% in the tree, and 92.7% in the sapling strata) among sites. Overall, our research revealed a gradient of soil fertility influencing species composition across different strata. Additionally, we discovered that preserved landscapes had a positive impact on species diversity within both strata. The species exclusivity in the sampled sites and the high turnover rate imply the need to consider multiple reference ecosystems when restoring the watershed to reduce the risk of biotic homogenization. Finally, the reference ecosystems defined here serve as a basis for the selection of locally particular species in the implementation of restoration projects that aim to improve biodiversity, ecosystem services, and water security. [Display omitted] •The world largest mining dam breach deeply impacted a hotspot watershed in Brazil.•We found low compositional similarity between riparian sites along Rio Doce watershed.•In both strata, >76% of the community occurred exclusively in one site.•Soil heterogeneity drive plant community distinctiveness along studied sites.•Restoration initiatives must take into account the idiosyncrasies of different sites.